Antimicrobial susceptibility and pathogenicity of Escherichia coli strains of environmental origin - Carvalho,Daiane (2015)
The study aimed to evaluate the antimicrobial susceptibility of 109 samples of Escherichia coli (E. coli) of environmental origin and to characterize these isolates according to the degree of pathogenicity in vivo, verifying a possible relationship between this variable and susceptibility to the active principles tested. The isolates were subjected to disc diffusion test to 14 antibiotics. From 16.5% to 90% of the samples were sensitive; 1 - 28.5% showed intermediate degree of susceptibility and between 9 to 78% of E. coli analyzed were resistant. The highest resistance percentages were seen in the class of quinolones and tetracyclines (>75%), and for sensitivity in the class of amphenicols (68.8%). By inoculating 1- day - old chicks, the isolates were classified as highly pathogenic (2.7%), intermediate (10.1%), low (42.2%) and apathogenic (45%). It was observed a wide variation in the susceptibility profile of isolates in relation to antimicrobials. It was also found that most of the samples had pathogenic potential (55%), thus being considered as APEC (avian pathogenic E. coli). No relationship between pathogenicity and antimicrobial susceptibility (P≤0.05) was observed.